Electroacupuncture improves TBI dysfunction by targeting HDAC overexpression and BDNF-associated Akt/GSK-3β signaling - Hung, Shih-Ya; Chung, Hsin-Yi; Luo, Sih-Ting; Chu, Yu-Ting; Chen, Yu-Hsin; MacDonald, Iona J.; Chien, Szu-Yu; Kotha, Peddanna; Yang, Liang-Yo; Hwang, Ling-Ling; Dun, Nae J.; Chuang, De-Maw; et al. (Frontiers in Cellular Neuroscience, 2022)
Background: Acupuncture or electroacupuncture (EA) appears to be a potential treatment in acute clinical traumatic brain injury (TBI); however, it remains uncertain whether acupuncture affects post-TBI histone deacetylase (HDAC) expression or impacts other biochemical/neurobiological events. Methods: We used behavioral testing, Western blot and immunohistochemistry analysis to evaluate the cellular and molecular effects of EA at LI4 and LI11 in both weight drop-impact acceleration model (WD)-and controlled cortical impact model (CCI)-induced TBI. Results: Both WD- and CCI-induced TBI caused behavioral dysfunction, increased cortical levels of HDAC1 and HDAC3 isoforms, activated microglia and astrocytes, and decreased cortical levels of BDNF as well as its downstream mediators phosphorylated-Akt and phosphorylated-GSK-3β. Application of EA reversed motor, sensorimotor, and learning/memory deficits. EA also restored overexpression of HDAC1 and HDAC3, and recovered downregulation of BDNF-associated signaling in the cortex of TBI mice. Conclusion: The results strongly suggest that acupuncture has multiple benefits against TBI-associated adverse behavioral and biochemical effects and that the underlying mechanisms are likely mediated by targeting HDAC overexpression and aberrant BDNF-associated Akt/GSK-3 signaling.